Implementation of HIV pre-exposure prophylaxis in Colombia - Mueses-Marín, Hector Fabio; Martínez-Buitrago, Ernesto; Gómez-Peñalosa, Sheila Andrea; Torres-Isasiga, Julián Andrés; Camargo-Plazas, Pilar; Arrivillaga-Quintero, Marcela; Bolívar-Rocha, María Camila; Alvarado-Llano, Beatriz Eugenia; Galindo-Orrego, Ximena; Martínez-Cajas, Jorge Luis (Interdisciplinary Journal of Epidemiology and Public Health, 2021)
HIV/AIDS continues to be a global public health problem. Colombia is no exception. New combined prevention approaches can help reduce HIV transmission, such as the use of HIV medications used as pre-exposure prophylaxis (PrEP), combined with the intensification of condom use, which can help end the epidemic by 2030, as proposed by UNAIDS.